Energy confinement of hydrogen and deuterium electron-root plasmas in the Large Helical Device. (22nd August 2018) - Warmer, Felix; Takahashi, H.; Tanaka, K.; Yoshimura, Y.; Beidler, C.D.; Peterson, B.; Igami, H.; Ido, T.; Seki, R.; Nakata, M.; Yokoyama, M.; Akiyama, T.; et al.
Abstract: The dependence of the energy confinement and energy transport on the isotope mass is a long-standing open question in the stellarator community. With the recent upgrade of the Large Helical Device to allow for deuterium plasma operation, systematic isotope experiments could be carried out for the first time in a major non-axisymmetric device. Within this framework, electron-cyclotron-resonance heated (ECRH) hydrogen and deuterium plasmas were investigated varying both density and heating power to establish a broad data set. Even at low power the central ECRH heating is sufficient to lead to stellarator-specific core-electron-root-confinement which features a peaked electron temperature profile and a positive radial electric field. For this data set, the energy confinement time and energy transport is investigated in detail and compared to the neoclassical theory. Over the whole data set, the energy confinement time of deuterium is statistically 10%–20% larger than in hydrogen indicating that the ' isotope effect ' also exists in non-axisymmetric devices. Both the electron and ion temperature are elevated in deuterium compared to hydrogen at the same effective absorbed power and density. From a neoclassical point-of-view, the electron-root and the positive electric field extend over nearly the entire plasma radius. Good agreement is found between the measured and theoretical neoclassical ambipolar electric field. The neoclassical energy-flux can account for up to half the experimental flux implying that turbulence is responsible for a significant fraction of the entire energy-flux.